Cilia structure and motility - King, Stephen M.; Pazour, Gregory J. (Burlington, MA Academic Press is an imprint of Elsevier, 2009)
Along with its companion volume on intraflagellar transport, this book provides researchers with a comprehensive and up-to-date source of methods for the analysis cilia and flagella, focusing primarily on approaches that have been devised or significantly extended since the last volume of Methods in Cell Biology on this topic (volume 47, 1995). Edited by Stephen M. King and Gregory J. Pazour, the newest installment of this highly acclaimed serial will serve as an essential addition to the study of cilia and flagella.--Provided by publisher.
Includes bibliographical references and index.
Keywords: Cilia and ciliary motion; Electronic books